Skewness and option bounds: Short variance swaps and variance risk premium - Huang, Junying (Institutional Knowledge at Singapore Management University, 2014)
Semi-parametric upper bounds for option prices and expected payoffs are derived for call options. These bounds depend only on the first three moments and not on the underlying stock distribution in general. Bounds on variance default swaps, a new asset, are derived.